Dehydration and the ripening of 'Hass' avocado fruit. Issue 2 (3rd July 2022) - Burdon, Jeremy; Billing, David; Kerr, Karen
ABSTRACT: Water loss from fruit, including avocado, has been reported to accelerate ripening. 'Hass' avocado fruit were imaged by MRI shortly after harvest and the proton density (PD) and spin-spin relaxation time constant T 2 data extracted for regions of interest. Water was then driven off at two rates (designated as Fast and Slow) with respiratory activity and ethylene production of the individual fruit monitored as non-destructive markers of ripening. Fruit from the Slow drying treatment ripened several days later, but with less water loss, than fruit from the Fast drying treatment. There was a correlation in the Slow drying treatment for fruit with higher PD and T 2 values to take longer to ripen. This trend was clearest for the inner mesocarp data. However, there was a weaker, inverse, relationship for fruit in the Fast drying treatment. Therefore, the relationship between water content and ripening seems to be affected by the rate of water loss. It is concluded that the capacity for water loss to accelerate avocado fruit ripening is confirmed. It also appears that MRI data collected at harvest may be indicative of the time that a fruit would naturally take to ripen.